Working without walls an insight into the transforming government workplace - Allen, Tim (DEGW, 2004)
"This book provides an accessible publication that captures and explores current UK government workplace developments and emerging good practice in order to inform, encourage and support wider improvement and innovation, across both the public and private sectors." -- Cover